1997
DOI: 10.1007/s004110050068
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and distribution of radiocaesium in broiler chicken

Abstract: The distribution and biological half-life of radiocaesium (137Cs) in broiler chickens after three oral applications (in course of 1 day at the age of 14 days) of artificially contaminated feed mixture were studied. There was a rapid uptake of the orally administered 137Cs (within a few hours) and also a rapid loss of 137Cs which varied in the different organs (the initial biological half-life was: liver 0.6 day, intestine 0.6 day, breast meat 2 days, leg meat 1.2 days). More than one-half of the total administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
7
2
Order By: Relevance
“…In leg meat of broilers which were killed after 24 h, the percentage of distributed 137 Cs was 39.4%, while a slight increase (53.5%) was observed in pheasants. Pöschl et al (1997) reported that the fraction of 137 Cs in leg chicken meat after a single contamination was 32%, which is somewhat lower than our results. In pheasants killed after 24 h, the distribution of 137 Cs in the leg meat was 53.5%, and it was higher than in broilers.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…In leg meat of broilers which were killed after 24 h, the percentage of distributed 137 Cs was 39.4%, while a slight increase (53.5%) was observed in pheasants. Pöschl et al (1997) reported that the fraction of 137 Cs in leg chicken meat after a single contamination was 32%, which is somewhat lower than our results. In pheasants killed after 24 h, the distribution of 137 Cs in the leg meat was 53.5%, and it was higher than in broilers.…”
Section: Discussioncontrasting
confidence: 84%
“…4 137 Cs activity concentration (Bq/kg) in pheasants breast meat after single contamination and protection with AFCF and clinoptilolite 137 Cs concentration in the breast meat of broilers increased from 6% to 16% as determined over 24 h. The obtained relative values are lower than those (18%) reported by Pöschl et al (1997). In contrast, the percentage of 137 Cs in breast meat of pheasants ranged from 10.6 to 26.2% and it was higher than in broilers.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations